2011
DOI: 10.1094/cchem-03-11-0026
|View full text |Cite
|
Sign up to set email alerts
|

Protein Extraction from Triticale Distillers Grains

Abstract: Triticale is being actively explored as a feedstock for bioethanol production in Western Canada. Triticale distillers grains, an important coproduct of the bioethanol industry, are used mainly as animal feed. This study aims to develop methods of protein extraction from triticale distillers wet grains and distillers dried grains with solubles. Osborne fractionation showed low protein extractability because excessive protein denaturation occurred during sample preparation. Five methods were used to extract prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…2,7 Historically, casein, gelatin, blood and soy proteins were applied for various adhesive applications. 2,4,8 More recently, the possibility of using other protein sources such as wheat gluten, 9 cottonseed protein, 10 triticale protein, 5,11 and canola protein 7 were studied.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Historically, casein, gelatin, blood and soy proteins were applied for various adhesive applications. 2,4,8 More recently, the possibility of using other protein sources such as wheat gluten, 9 cottonseed protein, 10 triticale protein, 5,11 and canola protein 7 were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al (2016) evaluated the differences in zein protein recovery using 13 different solvents (isopropanol, isoamyl alcohol, n‐butanol, isobutanol, 2,3‐butanediol, 1,4‐butanediol, tetrahydrofuran, 1,3‐dioxolane, 1,4‐dioxane, acetic acid, lactic acid, [emim]Ac, and [emim]Br) and found that isopropanol resulted in the highest extraction efficiency of 75%. Moreover, Bandara et al (2011) investigated the efficiencies of protein extraction from triticale‐DDGS using five methods (pH shifting, 60% ethanol, alkaline‐ethanol solution, glacial acetic acid, and enzyme‐aided extraction) and observed that the extracts obtained from alkaline‐ethanol and glacial acetic acid presented higher protein contents (61%–65%); however, the protein recovery was limited to 21%–23%. For sorghum‐DDGS, higher protein recovery of 44.2 and 56.8% were achieved using acetic acid and NaOH–ethanol treatment, respectively.…”
Section: Protein Extraction and Fractionationmentioning
confidence: 99%
“…In general, DDGS is mixed with a specific amount of enzyme and incubated to allow certain level of protein hydrolysis at optimal pH. Then, the enzyme is deactivated, and the supernatant is separated from slurry through centrifugation and then subjected to precipitation (pH shifting) or freeze‐drying (Bandara et al, 2011; Cookman & Glatz, 2009; Sari et al, 2014). For triticale‐DDGS, 75%–82% protein recovery was obtained by enzyme‐Protex 6L treatment (Bandara et al, 2011).…”
Section: Protein Extraction and Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity of proteins to pH, ionic strength, temperature, and processing conditions facilitates protein modifications to improve their functionality (Rajasekar et al, ). Several plant and animal protein sources have been explored in the past for adhesives development, including soy protein (Damodaran & Zhu, ; Kumar et al, ; Zhu & Damodaran, ), wheat gluten (WG) (Khosravi, Khabbaz, Nordqvist, & Johansson, ), CP (Bandara, ; Bandara et al, ; Bandara, Esparza, & Wu, ; Bandara & Wu, ; Bandara & Wu, ; Wang et al, ), cotton seed protein (Cheng, Dowd, & He, ; He, Chapital, Cheng, & Dowd, ), triticale protein (Bandara, Chen, & Wu, ; Bandara, Chen, & Wu, ), and spent hen proteins (Wang & Wu, ), among others.…”
Section: Canola Protein As An Alternate Source For Protein‐based Adhementioning
confidence: 99%